Fibromyalgia syndrome—a bodily distress disorder/somatic symptom disorder? - Winfried Häuser; Mary-Ann Fitzcharles; Peter Henningsen (PAIN Reports)
Abstract. Introduction:. The debate addressing the classification of chronic widespread pain as a physical disorder (fibromyalgia syndrome) [FMS] or a somatoform disorder according to psychiatric classification systems has continued for decades. Objectives:. The review aims to line out the new perspectives introduced by the 11th version of the International Classification of Diseases (ICD 11) of the World Health Organization (WHO). Methods:. Critical review of the classification criteria of fibromyalgia syndrome and bodily distress disorder in ICD 11. Results:. Fibromyalgia syndrome has been eliminated from the chapter of diseases of the musculoskeletal system and is now included in a chapter “Symptoms, signs, clinical forms, and abnormal clinical and laboratory findings, not elsewhere classified“. Previously, the ICD-10 diagnosis of somatoform disorder was often used by mental health care disciplines instead of the label FMS. Somatoform disorders category has been eliminated as a diagnostic category in the ICD-11 and the 5th version Diagnostic and Statistical Manual of Mental Disorders of the American Psychiatric Association (APA) and has been replaced with the new categories of bodily distress disorder (BDD) and somatic symptom disorder (SSD) respectively. For diagnosis, these latter mental disorders require at least one distressing somatic symptom (e.g. pain) plus positive psychobehavioral criteria, namely „excessive thoughts, feelings, or behaviours related to the somatic symptoms or associated health concerns“, without the condition that distressing somatic symptoms have to be medically unexplained. Conclusion:. We argue that the psychobehavioral criteria of BDD/SSD are imprecisely defined and can be misinterpreted as for „Excessive health concerns“ which may occur due to the many uncertainties surrounding FMS or „Excessive time devoted to the symptoms“ which may be related to patient self-management strategies.